Interactice technologies as inclusive practice - Semeniuk, Antonina A. (My University, 2024)
Education of children with special needs has often led to their isolation from society as well as normal life. Facing numerous challenges, specialized institutions (both preschool and school) did not contribute to their inclusion into society. Nowadays, technological progress facilitates the integration of learning interactive means into the educational process, especially for children with special needs, which undoubtedly contributes to their socialization, improving the situation within inclusive environment.
Keywords: ІТ; IT technologies; інклюзія; inclusion; навчальні матеріали; educational materials